Pencegahan Pernikahan Dini melalui Penanganan Psikososial Berbasis Komunitas di Pagatan Hulu: Early Marriage Prevention through Community-Based Psychosocial Intervention in Pagatan Hulu - Faz, Gerry Olvina; Erawati, Desi; Pamungkas, Ari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Early marriage issues must be a serious concern since it could lead to the quality of human resources problem in Indonesia in the next few years. Even though early marriage in Indonesia is illegal in Indonesia's law, the rate of early marriage is still high. Moreover, this problem should be solved, and a preventive approach is needed to overcome this problem. In this community service, Community-Based Research is used to strengthen the community. Its implementation has four main stages: laying the foundation, planning, information gathering/analysis, and acting on the findings. This service is for senior high school students in Pagatan Hulu, one of the areas with the highest number of marriages in Central Kalimantan. The activity implementation involved the Students Organization (OSIS) members as Catalysts. The activity results show that the catalysts can discuss this issue based on their experiences through Focus Group Discussions. Furthermore, the catalysts also carried out activities with eleven grade students, including sharing knowledge about Child Marriage and Its Impacts, Inspiration Sharing Talkshows, Planning Skills, and Overcoming the challenges skills.